Is physics asking for a new kinematics? - Aldrovandi, R. [UNESP]; Pereira, J. G. [UNESP] (World Scientific Publishing, 2008)
It is discussed whether some of the consistency problems of present day physics could be solved by replacing special relativity, whose underlying kinematics is ruled by the Poincaré group, with de Sitter relativity, whose underlying kinematics is ruled by the de Sitter group. In contrast to ordinary special relativity, which seems to fail at the Planck scale, this new relativity is universal, in the sense that it holds at all energy scales. © 2008 World Scientific Publishing Company.